The link between smart device use and ADHD—how can reading and physical activity make a difference? - Chen, C C; Lin, W Y; Zou, M L; Hsu, H W; Lin, W C; Chen, Y H (European journal of public health, 2023)
Abstract Background Attention deficit and hyperkinetic disorders (ADHD) lead to poor academic performance and relationship problems in schoolchildren. While improper use of smart devices was found to have a negative impact on children's attention and behavior, few studies used a computerized self-administered scale for children to assess suspected ADHD more accurately. Therefore, this study aimed to investigate impact of weekend smart device usage on ADHD and child behavior, as well as the moderating effect of children's reading habits and activity levels. Methods A total of 137 students aged 6-8 in Taiwan participated in this study between Dec 2022 and Mar 2023. Data was collected through the self-reported instruments of Child Behavior Checklist for Ages 6-18 to assess behavior and an online questionnaire to gauge smart device usage by parents. The Computerized Attention Diagnostic Assessment (CADA) was conducted by children to evaluate their attention performance. Multiple linear regression was used for analysis. Results After adjusting for potential confounders in a stratified analysis, we found that among children with less physical activities, higher smart device usage was associated with more anxious/depressed (β = 8.40, p < 0.01), social problems (β = 6.48, p = 0.01), and thought problems (β = 6.43, p = 0.02), while among those with higher activities, higher device usage was associated with better picture attention scores (β = 5.67, p = 0.0237). Meanwhile, children who don't read habitually, higher smart device usage was associated with more somatic complaints (β = 3.31, p = 0.0235). Conclusions We highlighted the modifying effects of reading and physical activities on the link between smart device usage and attention and behavioral problems. In this digital age, it is imperative to provide parents with guidance on how to encourage reading and physical activities to help children mitigate the negative impact of smart device usage, including attention deficit and emotional problems. Key messages • High device usage in inactive or non-reading children is linked to behavioral problems like anxiety, social issues, and somatic complaints. • Promoting physical activities and reading can mitigate negative effects of device usage, highlighting the need for parental guidance in the digital age.